Marx's philosophy of revolution in permanence for our day : selected writings - Dunayevskaya, Raya (Studies in critical social sciences, 2019)
Marx's Philosophy of Revolution in Permanence for Our Day , a selection of writings by the Marxist-Humanist philosopher and revolutionary Raya Dunayevskaya, brings out the contemporary urgency of Marx's work as a philosophy of revolution in permanence. That dialectic permeates the totality of Marx's body of ideas and activities. Major themes include Marx's transformation of the Hegelian dialectic; the inseparability of Marx's economics, humanism, and dialectic; the battle of ideas with post-Marx Marxism, beginning with Engels; Black liberation, internationalism, and women's liberation; today's burning question of the relationship between spontaneity, organization, and philosophy; the emergence of counter-revolution from within the revolution; and the problem of what happens after the revolution.